Józef Wojciechowski (pseud. Józef z Mazowsza). Zalążki opowieści historycznoliterackich - Makuch, Damian Włodzimierz (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article presents the figure of Józef Wojciechowski (1840–1879), a Warsaw poet who wrote under the pseudonym Józef from Mazovia during and after the January Uprising. The author presents several germs of history of literature stories which could discuss the biography and works of Wojciechowski. The focus is primarily on how Wojciechowski is present in his historical epoch and modern research, on biographical legends that can be constructed based on the source material, and on the appreciation of his work using categories characteristic of 19th-century research. The end of the article discusses Wojciechowski's views on positivism. The poet does not exclude the idealist tradition from the new era, which, according to the author of the article, can be treated as the germ of a new story about the second half of the century.